2017
DOI: 10.7150/jca.18457
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Cell Line Classification and Its Relevance with Breast Tumor Subtyping

Abstract: Breast cancer cell lines have been widely used for breast cancer modelling which encompasses a panel of diseases with distinct phenotypical associations. Though cell lines provide unlimited homogenous materials for tumor studies and are relatively easy to culture, they are known to accumulate mutations duringthe initial establishment and subsequent series of cultivations. Thus, whether breast cancer cell line heterogeneity reflects that of carcinoma remains an important issue to resolve before drawing any reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
900
3
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 941 publications
(954 citation statements)
references
References 61 publications
(119 reference statements)
42
900
3
9
Order By: Relevance
“…Expression of key breast cancer genes were examined ( Supplementary Figure 1), including hormone receptors (ESR1 for estrogen receptor, PGR for progesterone receptor, ERBB2 for human epidermal growth factor receptor 2), histology marker (CDH1 for E-cadherin) and proliferation indicator (MKI67 for Ki67). Consistent with the previous characterizations [25][26][27] , ESR1 was expressed higher in the six breast cancer cell lines compared to MCF10A or HEK293;…”
Section: Scrna-seq Of Breast Cancer Cell Linessupporting
confidence: 90%
“…Expression of key breast cancer genes were examined ( Supplementary Figure 1), including hormone receptors (ESR1 for estrogen receptor, PGR for progesterone receptor, ERBB2 for human epidermal growth factor receptor 2), histology marker (CDH1 for E-cadherin) and proliferation indicator (MKI67 for Ki67). Consistent with the previous characterizations [25][26][27] , ESR1 was expressed higher in the six breast cancer cell lines compared to MCF10A or HEK293;…”
Section: Scrna-seq Of Breast Cancer Cell Linessupporting
confidence: 90%
“…CIPp cells with human epidermal growth factor receptor 2 (HER‐2/neu)‐positive were originally extracted from a female dog diagnosed with CMTAC with regional lymph node metastasis at clinical stage IV . HER‐2/neu‐positive CMTs are associated with indicators of poor prognosis such as high clinical stage, histological grade and invasive type of growth, and these findings are compatible with those observed in human breast cancer . Spontaneous CMTAC has also been considered as a promising animal model of some histological subtype of human female carcinogenesis .…”
Section: Discussionsupporting
confidence: 81%
“…21,26 HER-2/neu-positive CMTs are associated with indicators of poor prognosis such as high clinical stage, histological grade and invasive type of growth, and these findings are compatible with those observed in human breast cancer. [5][6][7]27,28 Spontaneous CMTAC has also been considered as a promising animal model of some histological subtype of human female carcinogenesis. 3,4 In this study, we showed that CDV-L was able to infect, efficiently replicate in, and lyse CMTAC CIPp cells.…”
Section: Discussionmentioning
confidence: 99%
“…MDA-MB-231 is a TGFβ1 responsive cell line while SK-BR-3 cells are TGFβ1 resistance. 37 Furthermore, MDA-MB-231 cell line is a basal type while SK-BR-3 is a luminal-type breast cancer cell line, 38 and it has been shown that inhibition of MYC in basal-type BC cells by genetic or pharmacological methods leads to higher sensitivity to TGFβ-stimulated invasion and metastasis. 39 The same study also reported that the mentioned signaling loop only exists in basal BC cells, but not in luminal BC cells.…”
Section: Discussionmentioning
confidence: 99%